2020
DOI: 10.18632/aging.102917
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumor mutational burden and immune cell infiltration in esophageal cancer patients with or without radiotherapy

Abstract: Growing evidence highlighted the tumor mutational burden (TMB) as an important feature of carcinogenesis and therapeutic efficacy in esophageal cancer (EC). Our study aimed to explore the genomic landscape and the correlation between TMB and immune cell infiltration in EC patients with or without radiotherapy. The EC patients were categorized into high TMB (TMB-H) and low TMB (TMB-L) groups by the ESTIMATE algorithm, and subgroup analysis was performed based on receiving radiotherapy or not. Univariate regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 39 publications
(40 reference statements)
4
22
1
Order By: Relevance
“…While TMB has been found to be associated with either poor or favorable prognosis in other tumor types (31,32), the prognostic value of TMB in GEA is largely unknown. In patients with esophageal cancer, high TMB was associated with decreased OS among patients who did not receive radiotherapy, but not in the whole patient population (46). We also did not find a significant association of TMB with OS in patients with stage IVB GEA.…”
Section: Discussioncontrasting
confidence: 79%
“…While TMB has been found to be associated with either poor or favorable prognosis in other tumor types (31,32), the prognostic value of TMB in GEA is largely unknown. In patients with esophageal cancer, high TMB was associated with decreased OS among patients who did not receive radiotherapy, but not in the whole patient population (46). We also did not find a significant association of TMB with OS in patients with stage IVB GEA.…”
Section: Discussioncontrasting
confidence: 79%
“…However, the prognostic impact of mutational burden in different types of cancer remains controversial. Yuan et al [ 39 ] demonstrated that patients with higher mutational load had a worse prognosis in esophageal cancer[ 39 ], consistent with previous studies in clear cell renal cell carcinoma and prostate cancer[ 40 , 41 ], whereas bladder cancer with higher mutational load was associated with better outcomes[ 42 ]. In these previous studies, they used the median value as the cut-off to distinguish TMB-H and TMB-L groups.…”
Section: Discussionsupporting
confidence: 74%
“…A large number of studies have confirmed that tumor immune cell infiltration can affect the efficacy of chemotherapy and immunotherapy, and the prognosis of patients. [13][14][15] Our work has shown that there does exist a significant positive correlation between GPRIN1 and CD4 + T cell, M1macrophage infiltration, and GPRIN1 is also positively correlated with the biomarkers of these infiltrating immune cells. Therefore, immune cell infiltration may be involved in the occurrence and development of GPRIN1-mediated KIRP/LUAD.…”
Section: Discussionmentioning
confidence: 94%
“…Current studies of GPRIN1 are limited and insufficient. The Cancer Genome Atlas (TCGA) project has generated genomic, epigenomic, transcriptomic, and proteomic data for over 20 different cancer types [14][15][16][17][18][19][20][21]. These data sets provide broad insight into the underlying genetic aberrations existing across multiple cancer types.…”
Section: Introductionmentioning
confidence: 99%